2022
DOI: 10.1094/pdis-08-21-1675-re
|View full text |Cite
|
Sign up to set email alerts
|

A Laminarin-Based Formulation Protects Wheat Against Zymoseptoria tritici via Direct Antifungal Activity and Elicitation of Host Defense-Related Genes

Abstract: The present study aimed to evaluate the potential of the laminarin-based formulation Vacciplant® to protect and induce resistance in wheat against Zymoseptoria tritici, a major pathogen on this crop. Under greenhouse conditions, a single foliar spraying of the product two days before inoculation with Z. tritici reduced disease severity and pycnidium density by 42% and 45%, respectively. Vacciplant® exhibited a direct antifungal activity on Z. tritici conidial germination both in vitro and in planta. Moreover, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 63 publications
1
6
0
Order By: Relevance
“…PR proteins are a set of novel proteins mainly produced by various plant organs in lower amounts and directly linked with host defense, which hampers the pathogen progression [ 110 , 111 ]. The two important PR proteins, β-1,3-glucanase and chitinase, belonging to the PR 2 and PR 3 families, respectively, play pivotal roles in plant resistance [ [112] , [113] , [114] ]. Saravanakumar et al [ 115 ] demonstrated that when rice plants were treated with a consortium of Pseudomonas spp., higher accumulations of chitinase were found against the sheath rot pathogen caused by Sarocladium oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…PR proteins are a set of novel proteins mainly produced by various plant organs in lower amounts and directly linked with host defense, which hampers the pathogen progression [ 110 , 111 ]. The two important PR proteins, β-1,3-glucanase and chitinase, belonging to the PR 2 and PR 3 families, respectively, play pivotal roles in plant resistance [ [112] , [113] , [114] ]. Saravanakumar et al [ 115 ] demonstrated that when rice plants were treated with a consortium of Pseudomonas spp., higher accumulations of chitinase were found against the sheath rot pathogen caused by Sarocladium oryzae .…”
Section: Discussionmentioning
confidence: 99%
“…This prompt reaction has been linked to strong hydrogen peroxide (H 2 O 2 ) up-regulation Trouvelot, Varnier [ 31 ], [ 63 ], which could reduce stomatal opening and impair a pathogen’s penetration of the host [ 64 ]. A direct effect of LAM was found against Zymoseptoria tritici in wheat [ 65 ], but its role against P. viticola is controversial. Besrukow et al [ 66 ] observed impaired zoospore motility, and Mestre, Arista [ 67 ] identified an endo-β-1,3-glucanases able to exert a direct effect against DM, whereas Gauthier, Trouvelot [ 49 ] and Steimetz, Trouvelot [ 63 ] reported no direct effect of LAM on P. viticola .…”
Section: Discussionmentioning
confidence: 99%
“…To highlight the potential induced resistance effect by JA WSPs, treated seeds were water-washed after soaking, to remove any extract residues that could have a direct antifungal effect. Polysaccharides such as laminarin were reported to exert an antigerminative effect against the conidia of some fungi [64,65]. The polysaccharides extracted from JA might explain the elicitation of plant physiological responses against pathogens with the improvement of seedling emergence and plant growth, which may have concurred to the disease reduction.…”
Section: Discussionmentioning
confidence: 99%